Conditional 1-year outcomes after emergent conversion to open heart surgery during transcatheter aortic valve implantation: a propensity-matched landmark analysis - Nasso, Giuseppe; Vignaroli, Walter; Contegiacomo, Gaetano; Marchese, Alfredo; Greco, Ernesto; Fattouch, Khalil; Bonifazi, Raffaele; Fiore, Flavio; Schinco, Giacomo; Valenzano, Antongiulio; Solimando, Carlo; Margari, Vito; et al. (Frontiers in Cardiovascular Medicine, 2025)
BackgroundEmergent conversion to open heart surgery (E-OHS) during transcatheter aortic valve implantation (TAVI) is rare (0.5%–2%) but carries high perioperative mortality. Long-term outcomes in survivors beyond 30 days are not well defined.ObjectivesTo assess 1-year conditional outcomes in patients who survived ≥30 days post-TAVI, comparing E-OHS survivors with propensity-matched uncomplicated TAVI recipients.MethodsBetween January 2020 and August 2023, 825 consecutive TAVI procedures were performed at three Italian centers; 11 patients (1.3%) required E-OHS for catastrophic intraprocedural complications. A 30-day landmark analysis excluded early deaths (E-OHS: n = 3; controls: n = 25). Propensity matching (1:10) was performed on nine variables, yielding 8 E-OHS survivors and 80 well-matched controls.Primary endpointAll-cause mortality from day 31 to 1 year.Secondary endpointsComposite of death, moderate-or-greater paravalvular regurgitation, or valve reintervention; heart failure rehospitalization; permanent pacemaker; stroke/transient ischemic attack (TIA); and acute kidney injury (AKI).ResultsBaseline characteristics were comparable. The mean age was 77 ± 5 years; EuroSCORE II was 6.8 ± 2.1%. One-year conditional mortality was 0% in E-OHS survivors vs. 2.9% in controls (p = 0.64). The composite endpoint occurred in 12.5% vs. 13.6% (p = 0.88). Other outcomes were similar: heart failure rehospitalization (12.5% vs. 11.2%), pacemaker implantation (12.5% vs. 9.6%), stroke/TIA (0% vs. 1.2%), and AKI (0% vs. 7.2%). No structural valve deterioration or thrombosis was observed.ConclusionsE-OHS survivors who overcome the initial high-risk phase achieve 1-year outcomes comparable to standard TAVI patients. These findings support immediate surgical backup within TAVI programs and provide reassurance for high-risk patient counseling.